ANALISIS INTEGRASI DATA PADA RELASIONAL BASIS DATA DENGAN MENGGUNAKAN METODE SCHEMA MATCHING - Hammad, Rifqi (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2019)
University is one of the agencies that use information technology to support various business processes. University requires data integration between the systems so that the data available in one system can be used in other systems to support data management.In forwarding data integration there are several obstacles that occur one of the causes is schema heterogeneity used by each information system. linguistic method is one of the schema matching methods used to overcome the problem of schema heterogeneityBased on the analysis of database schemes with the linguistic method, the values of precision, recall and f measure are 0.75. This value indicates that the application of the matching schema has been quite good. But there are still some of the same data between the schemes so that the integration of the data owned is not maximal. So that optimization is still needed to maximize the data integration